2019
DOI: 10.7759/cureus.5707
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of Minimally Invasive Concomitant Aortic and Mitral Valve Replacement/Repair at a Tertiary Care Cardiac Centre of a Developing Country

Abstract: IntroductionMinimally invasive double valve replacement (DVR) surgery through a small transverse anterior thoracotomy is an alternate technique to sternotomy for concomitant aortic and mitral valve (AVR, MVR) surgery. The aim of this study was to evaluate the in-hospital and early outcomes of direct vision minimal invasive double valve surgery (DVMI-DVR) at a tertiary care cardiac center of a developing country.MethodsThis study was conducted at the National Institute of Cardiovascular Diseases Karachi, Pakist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Miura et al 26 did not find any significant difference between the groups (72 vs. 24 h; p = .23, respectively). Most non‐comparative studies using MIS report varying ICU stays of between 24 and 72 h, providing similar results to the MIS groups in the comparative studies 12,29,31,32 . One MIS study reported an ICU stay of 8.6 ± 3.2 h, 33 which was significantly lower than any other double valve MIS or MS ICU stay reported.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Miura et al 26 did not find any significant difference between the groups (72 vs. 24 h; p = .23, respectively). Most non‐comparative studies using MIS report varying ICU stays of between 24 and 72 h, providing similar results to the MIS groups in the comparative studies 12,29,31,32 . One MIS study reported an ICU stay of 8.6 ± 3.2 h, 33 which was significantly lower than any other double valve MIS or MS ICU stay reported.…”
Section: Discussionmentioning
confidence: 74%
“…Five non‐comparative double valve MIS studies reported this outcome, four of which found no sternal wound infection (SWI) post operatively 12,17,29,33 and one reported 1 case (1.3%) 18 . The three comparative studies which reported this outcome found no significant difference between the groups (MIS vs. MS: 0% vs. 0.04%, 26 1.2% vs. 0% 24 and 1.1% vs. 3.3% 25 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…ONCAB and valvular procedures were performed through median sternotomy with target activated clotting time above 480 seconds and myocardial protection using St. Thomas cardioplegia delivered antegrade (graft plegia was preferred by few surgeons) or retrograde with topical cooling. Minimally invasive atrial septal defect (ASD) closure was performed using the same technique as described in our previous publication on double valve replacement with central cannulation [9].…”
Section: Methodsmentioning
confidence: 99%